2015
DOI: 10.1016/j.ymgmr.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic autopsy with next generation sequencing in sudden unexpected death in infancy: Postmortem diagnosis of fatty acid oxidation disorders

Abstract: The recent introduction of metabolic autopsy in the field of forensic science has made it possible to detect hidden inherited metabolic diseases. Since the next generation sequencing (NGS) has recently become available for use in postmortem examinations, we used NGS to perform metabolic autopsy in 15 sudden unexpected death in infancy cases. Diagnostic results revealed a case of carnitine palmitoyltransferase II deficiency and some cases of fatty acid oxidation-related gene variants. Metabolic autopsy performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Recent molecular autopsy studies have identified inherited metabolic disease and arrhythmia as a possible cause of SUD, but in Japan there have been few studies on sudden infant death (Table ). In our previous metabolic autopsy and arrhythmia‐related molecular autopsy studies, we noted that some cases of SUD were caused by these diseases, but only a small number of cases involved disease‐causing gene variants, and most cases were not explained by mutations of these genes.…”
Section: Single Nucleotide Variants: Genotype Distribution Vs Sud Statusmentioning
confidence: 95%
“…Recent molecular autopsy studies have identified inherited metabolic disease and arrhythmia as a possible cause of SUD, but in Japan there have been few studies on sudden infant death (Table ). In our previous metabolic autopsy and arrhythmia‐related molecular autopsy studies, we noted that some cases of SUD were caused by these diseases, but only a small number of cases involved disease‐causing gene variants, and most cases were not explained by mutations of these genes.…”
Section: Single Nucleotide Variants: Genotype Distribution Vs Sud Statusmentioning
confidence: 95%
“…From the 17 undiagnosed cases, 9 patients’ parents gave consent for whole-genome sequencing. One of the nine cases was diagnosed with carnitine palmitoyltransferase II deficiency by metabolic autopsy 26 . In another case, we could not extract a sufficient amount of DNA for targeted gene-sequencing panel analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[20,21] Tests for assessing inherited metabolic disorders were conducted nationwide in the routine examination for newborns. [22] Genetic testing for arrhythmic disorders was also conducted for cases examined in this study. [23] Data used for analysis consisted of DSI information, therapeutic information in emergency care, and maternity passbook.…”
Section: Methodsmentioning
confidence: 99%